Possible contribution of TED6 and TED7, secondary cell wall-related membrane proteins, to evolution of tracheary element in angiosperm lineage - Rejab, N.A.; Nakano, Y.; Yoneda, A.; Ohtani, M.; Demura, T. (2015)
The Tracheary Element Differentiation-Related6 (TED6) and TED7 membrane proteins function in the differentiation of xylem vessel elements, the cellular units for water conduction in angiosperm plants. Functional analysis of TED6 and TED7 had suggested that these proteins directly bind to a subunit of the secondary cell wall (SCW)-related cellulose synthase complex, to promote SCW formation in xylem vessel elements. However, whether TED6 and TED7 function in SCW formation of xylem vessel elements only, or function broadly in other cell types has remained unclear. To clarify this, we conducted detailed expression analysis of TED6 and TED7 genes in Arabidopsis thaliana. This showed that TED6 and TED7 are expressed in differentiating vessel elements of all organs examined here, including roots, leaves, and inflorescence stems. We detected no TED6 and TED7 promoter activity in other types of cells with SCW thickening, such as fiber cells and anther endothecium, indicating that TED6 and TED7 have specific roles in SCW formation of vessel elements. Homology searches identified TED6/7-like proteins only in the angiosperm lineage. These data suggest that development of TED6/7 proteins could have coincided with the emergence of the angiosperm lineage, and that TED6/7 may have made key contributions to the evolution of water-conducting cells from tracheids to vessels.